A Comparative Study on Shi‘îte Tafsîr of the Qur’an 24: 55 and the Bible Isaiah 11:1-9: Theology of Hope in the Concept of Mahdism and Messianism - Luthfi Rahman (Jurusan Tafsir Hadis Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
This paper engages with the theological discourse on the state of al-Mahdi in Shi‘i tradition and the Peaceful Kingdom of Christianity. It focuses on two particular narratives, Quranic one focusing on Shi‘i tafsir Qur’an 24:55 and Biblical one concerning on Isaiah 11:1-19. This study employs library research looking specifically at Qur’anic and Biblical commentaries. By comparing the texts, it is found out that the first insists on several requirements to realize the promise of God (the state of al-Mahdî) by performing active struggles i.e. possessing strong faith and doing righteous action. On the other hand, the latter provides the description of the ideal circumstance when Messiah comes to a region in which both the ruler and the ruled do active struggles. The first still emphasizes the importance of strong faith while the second doesn’t. Yet, both narratives share that active struggles and righteous actions must be at stake.